HEALTH, ENVIRONMENT, ANCESTRALITY: A UNIVERSITY EXTENSION EXPERIENCE IN AGROECOLOGY - Missagia de Mattos , Izabel (2024)
In search of building paths for lasting and sustainable social development, the City of Maricá, through the Maricá Development Company (Codemar), has been making investments in research, extension and innovation in Agroecology. Through an agreement between UFRRJ and Codemar, the Inova Agroecologia Maricá Project was created in 2021. This article describes the action research initiatives focusing on the relationship between health and the environment, carried out by the Health Axis of the aforementioned project. It is considered relevant to present both the participatory methodology used in the project and which resulted in the Raízes Maricá event, and to highlight the potential for articulation between universities, public authorities and social movements in the construction of sustainable and socially fair futures.